Climate mediates the effects of disturbance on ant assemblage structure - Gibb, H.; Sanders, N.; Dunn, Robert; Watson, S.; Photakis, M.; Abril, S.; Andersen, A.; Angulo, E.; Armbrecht, E.; Aman, X.; Baccaro, F.B.; Bishop, T.; et al. (The Royal Society Publishing, 2015)
Many studies have focused on the impacts of climate change on biological assemblages, yet little is known about how climate interacts with other major anthropogenic influences on biodiversity, such as habitat disturbance. Using a unique global database of 1128 local ant assemblages, we examined whether climate mediates the effects of habitat disturbance on assemblage structure at a global scale. Species richness and evenness were associated positively with temperature, and negatively with disturbance. However, the interaction among temperature, precipitation and disturbance shaped species richness and evenness. The effect was manifested through a failure of species richness to increase substantially with temperature in transformed habitats at low precipitation. At low precipitation levels, evenness increased with temperature in undisturbed sites, peaked at medium temperatures in disturbed sites and remained low in transformed sites. In warmer climates with lower rainfall, the effects of increasing disturbance on species richness and evenness were akin to decreases in temperature of up to 9°C. Anthropogenic disturbance and ongoing climate change may interact in complicated ways to shape the structure of assemblages, with hot, arid environments likely to be at greatest risk.